2012
DOI: 10.1021/om201134j
|View full text |Cite
|
Sign up to set email alerts
|

Rhodium(III)-Catalyzed Hydroamination of Aromatic Terminal Alkynes with Anilines

Abstract: Society. It incorporates referee's comments but changes resulting from the publishing process, such as copyediting, structural formatting, may not be reflected in this document.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 58 publications
2
21
0
Order By: Relevance
“…7 The hydroamination of alkynes and alkenes is an atom economical method for the synthesis of C-N bonds and can be catalysed by lanthanides, actinides as well as early and late transition metal complexes. [8][9][10][11][12][13][14][15][16][17][18][19] Finding catalysts that are stable as well as effective for promoting a range of different hydroamination reactions remains an important challenge. Late transition metal complexes have lower oxophilicity and higher functional group tolerance in comparison to lanthanides, actinides and early transition metal complexes, and hence have great potential for a wider application as hydroamination catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…7 The hydroamination of alkynes and alkenes is an atom economical method for the synthesis of C-N bonds and can be catalysed by lanthanides, actinides as well as early and late transition metal complexes. [8][9][10][11][12][13][14][15][16][17][18][19] Finding catalysts that are stable as well as effective for promoting a range of different hydroamination reactions remains an important challenge. Late transition metal complexes have lower oxophilicity and higher functional group tolerance in comparison to lanthanides, actinides and early transition metal complexes, and hence have great potential for a wider application as hydroamination catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…5a-b,12 In an earlier study, we have found that [Cp*RhCl 2 ] 2 , 1 catalyses the hydroamination of terminal alkynes with anilines to afford ketimines. 13 Since 1 can effectively cyclometallate aromatic imines in the presence of acetate, we thought that the two separate steps may be combined to yield N-containing cyclometallated rhodium complexes in a single step. To the best of our knowledge, there is only one report of a similar strategy, which involves the single step synthesis of alkenyl ketone rhodium complexes using water and phenylacetylenes.…”
Section: Introductionmentioning
confidence: 99%
“…A crystal structure of the Rh III aniline complex, [Cp*RhCl 2 (NH 2 Ph)] (Cp* = pentamethylcyclopentadienyl) has been reported 25. The Rh–N aniline bonds of complexes 1 [2.144(3) Å], 4 ‐OTf [2.120(9) and 2.132(8) Å], and 7 [2.117(3) Å] are slightly shorter than that of [Cp*RhCl 2 (NH 2 Ph)] [2.185(1) Å] 25.…”
Section: Resultsmentioning
confidence: 99%
“…A crystal structure of the Rh III aniline complex, [Cp*RhCl 2 (NH 2 Ph)] (Cp* = pentamethylcyclopentadienyl) has been reported 25. The Rh–N aniline bonds of complexes 1 [2.144(3) Å], 4 ‐OTf [2.120(9) and 2.132(8) Å], and 7 [2.117(3) Å] are slightly shorter than that of [Cp*RhCl 2 (NH 2 Ph)] [2.185(1) Å] 25. The N–C ipso bond length of [Cp*RhCl 2 (NH 2 Ph)] [1.446(2) Å]25 is of a similar magnitude to those of the complexes reported herein [ 1 , 1.429(5) Å; 4 ‐OTf, 1.44(2) and 1.46(2) Å; and 7 , 1.443(4) Å].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation